2021
DOI: 10.30737/agrinika.v5i1.1521
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan KNO3 pada Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jack) Fase Pre-Nursery

Abstract: Fulfillment of quality seeds in the effort of increasing oil palm productivity can be done by means of appropriate fertilization. One of the fertilizers that can be used to optimize seedling growth in the pre-nursery is by using KNO3. The objective of this research was to find out KNO3 concentration in optimizing the growth of oil palm seedlings in the prenursery phase. The research was conducted in the Oil Palm Nursery Unit of Politenik Negeri Lampung. The experimental design used was a single treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…The results in this study align with the research of Usodri et al (2021), which showed that the application of slowrealese fertilizer optimized the growth of hybrid corn seedlings in the main nursery on all observed observation variables. In addition, Hutapea et al (2014) added that slow-release fertilizer could spur the growth of downy mildew-infected corn on the growth variables of stem diameter, number of leaves, and plant height.…”
Section: Growth Of Downy Mildew-affected Maize Applied With Slow Rele...supporting
confidence: 90%
“…The results in this study align with the research of Usodri et al (2021), which showed that the application of slowrealese fertilizer optimized the growth of hybrid corn seedlings in the main nursery on all observed observation variables. In addition, Hutapea et al (2014) added that slow-release fertilizer could spur the growth of downy mildew-infected corn on the growth variables of stem diameter, number of leaves, and plant height.…”
Section: Growth Of Downy Mildew-affected Maize Applied With Slow Rele...supporting
confidence: 90%